PROMOTING EXTENSIVE READING ACTIVITY THROUGH CONSTRUCTING READING LOGS PROJECT IN EFL CLASS - Aulia, Vivi (Lembaga Penelitian Universitas Swadaya Gunung Djati Cirebon, Indonesia, 2019)
This research aims at knowing the result of students’ extensive reading (ER) activities that were described on reading logs project carried out by English Department students of STKIP PGRI Banjarmasin. Besides that, this research also wants to know the students’ attitude towards the ER activity by gaining their personal views on the benefits and difficulties faced by them in accomplishing the activity. This research takes place towards 22 students who are assigned to do ER activity outside the class time. The data were collected through the documentation of their reading logs project and the questionnaire. The reading logs project consists of six elements that are reported by students individually presenting the summary of their reading activities during 16 weeks while the questionnaire gains information further on clarifying the benefits and the difficulties they face on the activity. The result of documentation students’ reading logs project shows that the students are comfortable having freedom to choose reading material based on genre determined and its sources, stating specific reason on choosing reading material, and reflecting what has been discovered while reading. Furthermore, the result of questionnaire shows that students have benefits and difficulties in promoting ER activity through constructing reading logs project. Since they are given freedom on this activity, 100% of them state that ER activity is not easy due to limitation of their free time during the large amount of other courses assignment. This research concludes that promoting ER to build students’ reading habit and reading culture should be developed continually.